The Optimization Using Electric Ground Support Equipment in Aviation Industry - Sari, Mustika; Wan Mohamed, Wan Mazlina; Jalil, Siti Ayu (International Journal of Energy Economics and Policy, 2022)
An airport is one of the country’s infrastructures that provides air transportation services. In providing its services, To ensure aircraft safety, airports must conform to a set of international technical operating standards and planned operating procedures. In addition, airports also have a social responsibility to prevent pollution and support eco green. Therefore, this study aims to conduct a benefit cost analysis using electric ground support equipment in aviation industry, both for using e-GSE using diesel and using e-GSE using electricity. The method used in this research is the Benefit Cost Ratio method. Based on the research results, it shows that the use of e-GSE using both diesel and electricity is feasible because it has an net present value (NPV) value of more than 0. However, when compared with the assumption of 25 years of use, the use of e-GSE using diesel is considered more profitable than using electricity.